Vulneración De Los Principios De Celeridad Y Eficacia En El Trámite De La Garantía Jurisdiccional De Habeas Corpus, Interpuesto Por Personas Privadas De Libertad - Paqui Vega., Jonnathan Francisco (2023)
The present academic research work is carried out in the legal field of constitutional law, with a pragmatic-legal problem that has been delimited with the topic: VIOLATION OF THE PRINCIPLES OF SPEED AND EFFECTIVENESS IN THE PROCESSING OF THE JUDICIAL GUARANTEE OF HABEAS CORPUS, FILED BY PERSONS DEPRIVED OF LIBERTY. The purpose of this investigation is to demonstrate the violation of the principles of speed and effectiveness in the processing of the judicial guarantee of habeas corpus, when the person who files it is a person deprived of liberty, resulting in a legal problem that has an impact on the rights of these people, who are within the priority attention groups. This topic has two approaches, on the one hand. The present topic has two approaches, on the one hand, to demonstrate the violation of rights of persons deprived of their liberty and, on the other, to reflect the setbacks they present when filing a constitutional habeas corpus action. The main objective of this investigation is to establish a legal criterion related to the problems that occur within the judicial system at the moment of knowing jurisdictional guarantees such as Habeas Corpus. In addition, another section of the present academic research work analyzes resolved cases that are closely related to the problems raised, showing that within legal practice these conflicts are presented. Finally, from the research carried out with the application of surveys and interviews with professionals and legal specialists, results were obtained which are represented graphically, they were used to analyze, make conclusions and recommendations regarding the violation of the speed and effectiveness of the habeas corpus procedure.